Pengaruh Penghindaran Pajak (Tax Avoidance) Terhadap Biaya Utang (Study pada Perusahaan Food and Beverages di Bursa Efek Indonesia 2018-2020) - Abdullah Musaddad; Rachma Agustina (Prodi Akuntansi Fakultas Ekonomi Universitas Hasyim Asy'ari, 2022)
This study aims to determine the effect of tax avoidance on the cost of debt in food and beverages companies on the IDX for the 2018-2020 period. Using quantitative methods with secondary data in the form of financial statements of food and beverages companies on the IDX for the 2018-2020 period. Sampling used purposive sampling of 14 food and beverages companies on the IDX for the 2018-2020 period. The data is processed using SPSS with the results of the study showing that tax avoidance has no effect on the cost of debt. Keywords: Tax Avoidance ; Cost of Debt